Effect of shadowing on the performance of space-time trellis-coded systems. - Uysal, M.
We analyze the performance of space-time trellis codes over shadowed Rician fading channels. The shadowed Rician channel is a generalization of the Rician model, where the line-of-sight path is subjected to a lognormal transformation due to foliage attenuation, also referred to as shadowing. Using the moment generating function method, we derive an exact expression for the pairwise error probability (PEP) of space-time trellis coded systems operating over this channel. The asymptotic analysis of PEP shows that the design criteria of space-time trellis codes proposed for Rayleigh fading still hold when used over shadowed Rician channels. We also present simulation results for bit-error rate performance under various degrees of shadowing.
Keywords: MIMO channels; Rician fading channels; Asymptotic analysis; Bit error rate performance; Foliage attenuation; Line-of-sight path; Lognormal transformation; Moment generating function method; Multiple input multiple output channels; Pairwise error probability; Shadowing; Space-time trellis coded systems